Pendampingan Pelatihan Sistem Pencatatan Inventaris Berbasis Android dan Website Pada SDN 1 Tumbakbayuh, Kabupaten Badung - Nyoman Purnama; Nengah Widya Utami (Jurnal Pengabdian kepada Masyarakat Radisi, 2023)
Technology has a very large influence in people's lives. Technology in data management using information systems, is something that needs to be done in various aspects of life. With the existence of an information system will facilitate the management and storage of data. Management of inventory data using an information system is implemented in SD No. 1 Tumbakbayuh. This elementary school is an elementary school located at Br. Danginsema, Tumbakbayuh, Mengwi, Badung district, Bali province. In this service activity, an inventory information system is built that is useful for managing inventory in schools. In addition to making website and mobile-based applications aimed at the administration section and school principals at SDN 1 Tumbak Bayuh, outreach was also implemented which aimed to provide understanding to the school regarding the important role of information technology in the field of inventory management. Based on the results of the assistance and socialization that has been implemented, the school has been greatly assisted in terms of digital-based school inventory management.